(untitled) (Research, Society and Development, 2022)
In Brazil, breast cancer is the leading cause of death among women. Therefore, it is necessary to carry out pharmaceutical assistance actions during the treatment of these patients. This integrative review aimed to evaluate the available bibliographies on the importance of the pharmacist in promoting pharmaceutical care actions for patients with breast cancer. The research was carried out in February and March 2022 in the following databases: Scielo, BVS and Google Scholar, using the descriptors: “pharmaceutical assistance”; “breast cancer” and “pharmacotherapy”. The time frame was from 2017 to 2022. After using the aforementioned inclusion and exclusion criteria, 14 studies were retrieved. The main topics addressed in the recovered material were categorized and divided into three thematic axes: Access to medicines and knowledge of the multidisciplinary team, pharmacotherapeutic follow-up, health education and the role of the pharmacist. It is possible, through this work, to highlight the importance of the pharmacist for an improvement in the quality of life of the patient, through health education and participation with the multidisciplinary team.